Factors associated with mosquito control among construction workers: a systematic review - Dapari, Rahmat; Mohd Fadzil, Muhammad Fahmi; Hanzir, Muhammad Yazid; Mohamed Jais, Jamal Sham (Public Library of Science, 2024)
Introduction: Workers in the construction industry frequently work in construction sites with numerous areas that can potentially accumulate water, such as tanks, wet cement surfaces, or water puddles. These water collection sites become ideal breeding grounds for mosquito infestation, which leads to a higher prevalence of mosquito-borne diseases, especially malaria and dengue among construction workers. Despite that numerous factors have been identified in controlling vector-borne diseases, the specific factors that influence mosquito control at construction sites have yet to be explored. Aims: This systematic review aims to determine the factors associated with mosquito control among construction workers. Methods: Primarily, articles related to factors associated with mosquito control among construction workers were collected from two different online databases (ScienceDirect and EBSCOhost). Two independent reviewers were assigned to screen the titles and abstracts of the collected data, stored in Microsoft Excel, against the inclusion and exclusion criteria. Afterwards, the quality of the included articles was critically assessed using the Mixed Method Appraisal Tool (MMAT). Of the 171 articles identified, 4 were included in the final review. Results: Based on the thorough evaluation, mosquito-related knowledge, practical mosquito prevention measures, and Larval Source Management (LSM) were identified as vital factors associated with mosquito control among construction workers. The significant association between mosquito-related knowledge and control practices indicates higher knowledge linked to effective practices, particularly among female workers and those who were recently infected with malaria. Concurrently, there were notable challenges regarding sustainable preventive measures and larval control methods in construction settings. Conclusion: Implementing effective mosquito control, including knowledge and practice on mosquito control together with vector control, is highly required to suppress the expanding mosquito population. It is recommended that employers provide continuous mosquito control education and training to their employees and reward them with incentives, while employees should comply with the guidelines set by their employers to ensure successful mosquito control and reduce the spread of mosquito-borne diseases in the construction industry.